64 Image optimisation in micro computed tomography. (4th October 2017) - Simcock, IC; Hutchinson, JC; Shelmerdine, SC; Matos, J Novo; Sebire, NJ; Arthurs, OJ
Abstract : Background: Micro Computed Tomography (Micro CT) allows high resolution imaging using a multi-detector X-ray source to give 3D imaging reconstruction of tiny objects at micron resolution. Through a strong industrial collaboration between Great Ormond Street Hospital Children's Charity and Nikon Metrology Ltd, we installed the world's first micro CT scanner in a children's hospital worldwide in 2016. We have recently published detailed micro CT imaging in a variety of different settings, including craniopharyngioma phenotyping (Apps JR et al., 2016) and fetal organ imaging. (Hutchinson et al., 2016, 2017). Methods: In order to image human surgical specimens or fetal organs as part of a post mortem assessment, the addition of iodine is necessary to enhance soft tissue contrast for diagnostic purposes. This study empirically assessed the iodination optimisation protocol to allow high tissue contrast in feline cardiac samples, which would allow the protocol to be transferred to human samples. Results: We present the preliminary results from feline cardiac tissue preparation optimisation where signal to noise, contrast to noise, and depth of tissue penetration were quantitatively assessed. Conclusion: This is a sub-study as part of a larger trial in collaboration with the Royal Veterinary College into an animal model of hypertrophic cardiomyopathy, and has implications for the study of this disease in humans.